Kinetic and Thermodynamic Characterization of the Protease from Bacillus licheniformis (ATCC 12759) - Vivi Mardina; Faridah Yusof; Md. Zahangir Alam (Elkawnie: Journal of Islamic Science and Technology, 2020)
Abstract: In this study, the kinetic of a thermo-stable extracellular protease produced by Bacillus licheniformis (ATCC 12759) cultured in skim latex serum fortified media was investigated. The enzyme was stable up to 65 oC after incubation for 60 min at pH 8. The Lineweaver-Burk exhibited vmax (maximum rate) of 37.037 U/mg min-1 and KM (Michaelis-Menten constant) of 8.519 mg/mL. The activation energy (Ea) of casein hydrolysis and temperature quotient (Q10) were found to be 4.098 kJ/mol and 1.038 - 1.034, respectively, at a temperature ranging from 35 oC to 65 oC. The results of the residual activity test allowed estimating activation energy for irreversible inactivation of the protease (denaturation) which was approximately Ea(d) = 62.097 kJ/mol. The thermodynamic parameters for the enzyme irreversible denaturation were as follow enthalpy (59.286 ≤ΔH*d≥ 59.535 kJ/mol), Gibbs free energy (97.375 ≤ ΔG*d≥ 93.774kJ/mol), and entropy (-122.797 ≤ ΔS*d≥ -101.992 kJ/mol). These thermodynamic parameters inferred that the thermo-stable proteases could be potentially important for industrial application, for example, in the detergent industries.Abstrak: Pada penelitian ini, kinetika protease ekstraseluler termo-stabil yang diproduksi oleh Bacillus licheniformis (ATCC 12759), yang dikultur dalam media yang diperkaya serum lateks skim diselidiki. Enzim stabil hingga 65 oC setelah diinkubasi selama 60 menit pada pH 8. Lineweaver-Burk menunjukkan vmax (laju maksimum) adalah 37.037 U/mg min-1 dan KM (konstanta Michaelis-Menten) 8.519 mg/mL. Energi aktivasi (Ea) dari hidrolisis kasein dan suhu quotient (Q10) ditemukan masing-masing sebesar 4.098 kJ/mol dan 1.038 - 1.034, pada suhu yang berkisar dari 35 oC hingga 65 oC. Hasil uji aktivitas residu memungkinkan estimasi energi aktivasi untuk inaktivasi ireversibel dari protease (denaturasi) yang kira-kira Ea (d) = 62.097 kJ/mol. Parameter termodinamika untuk denaturasi enzim ireversibel adalah sebagai berikut entalpi (59.286 ≤ΔH * d≥ 59.535 kJ / mol), energi bebas Gibbs (97.375 ≤ ΔG * d≥ 93.774kJ / mol) dan entropi (-122.797 ≤ ΔS * d≥ -101.992 kJ / mol). Parameter termodinamika pada penelitian ini menyimpulkan bahwa protease termo-stabil dapat berpotensi penting untuk aplikasi industri seperti dalam industri deterjen.